Sound velocity and loss factor of polyurethane composites. Part I. - BANDERA, W.; PAWLACZYK, K. (Archives of Acoustics, 1991)
The paper reports development of elastic, unfoamed polyurethane compositions to be used as vibro-insulating materials. The examined compositions were prepared using poly(propylenoethers) of different molecular weights, toluylene diisocyanate and glass microspheres separated from fly-ashes. The effect of varied proportions of components on visco-elastic properties of the material, that is on sound velocity and loss factor was examined experimentally. The measurements were taken at room temperature within frequency range of 20Hz to 1000Hz. It was discovered that modification of the polyurethane binder content and alteration of the number of microspheres in a composition permit modification of properties of the material and especially its stiffness and internal damping.